Achieving equity and excellence : immediate results from the lessons of high-poverty, high-success schools - Reeves, Douglas B., 1953- (Solution Tree Press, 2019)
"In Achieving Equity and Excellence: Immediate Results From the Lessons of High-Poverty, High-Success Schools, author Douglas Reeves provides a methodology for change based upon identifying, recording, and replicating positive results in the readers' schools and communities. Dr. Reeves notes the need for immediate results and programs that are proven to work within readers' communities, as well as the urgent desire that educators have to create a more just and equitable system for their students. As such, this book serves as a research-backed guide for readers who wish to see their students make dramatic improvements in school in a single semester. Readers will study the mindset of high-poverty, high-success schools and the research that this mindset is founded on. Then, they will see how this mindset translates into a methodology of action for change that is based primarily in daily decisions that the readers will make for the benefit of their students. Through this book, readers will not only realize that a more equitable and just system is possible in their school, but also learn the mindset and practices necessary to make these changes a reality"--